Proposal for Training Caregivers as Health Promoters - Guadalupe Nieves Sevilla Gómez; María Magdalena López Rodríguez del Rey (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2015)
Background: caregivers are people without professional training who receive courses and seminars in schools for home caregivers and social institutions since their entry into the system. However, their training as health promoters is still inadequate. Objective: to design a program for training caregivers in senior citizens´ homes as health promoters. Methods: a pedagogical research was carried out in the province of Cienfuegos aimed to design a training program for caregivers. A survey to determine the training needs of caregivers was conducted together with a semi-structured interview to determine the experiences and knowledge provided to them. The focus group technique with ten specialists of the National Comprehensive Program for the Elderly and directors of senior citizens´ homes was used to determine the health promotion actions included in the training of these personnel. Results: a program for training caregivers as health promoters was designed. It consists of a course (theoretical and practical update and practical training in participatory techniques for the elderly) divided into 96 hours. The rationale, feasibility, relevance, sustainability, transferability, characterization and objectives of the program are described as well as the literature to be used. Conclusions: the design and implementation of this practical and participatory program will allow assuming health promotion as part of the caregivers´ work in senior citizens´ homes.